Evaluasi Perawatan Apeksifikasi Melalui Gambaran Radiografi pada Gigi Permanen Muda - Naufal Nurrizka Hibatullah; Lasmi Dewi Nurnaini (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Immature permanent teeth with open apices and pulpal necrosis present a significant challenge in endodontic treatment. Apexification procedures have been developed to stimulate the formation of a hard tissue barrier at the apex, thereby allowing adequate obturation. Objective: This case report aims to describe the evaluation of apexification treatment based on radiographic findings. Case Report: An 8-year-old boy accompanied by his mother presented to PKU Muhammadiyah Surakarta Hospital with a history of a fall one week earlier. The affected tooth had previously received a temporary restoration from another dentist. According to the patient’s mother, medication had been placed in tooth to devitalize the pulp prior to temporary filling. Clinical examination revealed that tooth 11 exhibited a fracture involving approximately half of the crown and extending into the pulp chamber. Discussion: Initial radiographic examination in 2018 indicated that immature teeth have lower structural resistance compared with mature teeth; therefore, endodontic intervention such as apexification is required to establish apical barrier and adequate obturation. The material used for apexification in this case was a combining calcium hydroxide and iodoform. In contrast to the initial stage, radiographic evaluation in 2024 demonstrated that root development had progressed to stage V. According to Cvek’s classification of root development, stage V (Cvek stage V) represents a condition in which root development is fully completed. Conclusion: Based on long-term clinical and radiographic evaluation in this case, apexification treatment proved effective in stimulating the formation of an apical barrier and supporting root maturation in immature permanent teeth.